2008
DOI: 10.4314/ajtcam.v4i3.31225
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Of Some Indian Medicinal Plants

Abstract: The antimicrobial potential of seventy-seven extracts from twenty-four plants was screened against eight bacteria and four pathogenic fungi, using microbroth dilution assay. Lowest concentration of the extract, which inhibits any visual microbial growth after treatment with p-iodonitrotetrazolium violet, was considered to be minimum inhibitory concentration (MIC). Water extracts of Acacia nilotica, Justicia zelanica, Lantana camara and Saraca asoca exhibited good activity against all the bacteria tested and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 7 publications
4
104
2
1
Order By: Relevance
“…Loizzo et al (2010) reported the antibacterial activity of total water extract, ethyl acetate and aqueous fractions from the leaves of . Antimicrobial A. heterophyllus activity of the plant extract was considered to be good if its MIC was less than 100µg/ml, moderate if MIC was from 100.0 to 500.0µg/ml and poor over 500.0µg/ml (Dabur et al, 2007). Since the MIC of the methanol extract of the plant against all the microbial strains were less than 100µg/ml, the methanol extract can be considered as a good quality.…”
Section: Discussionmentioning
confidence: 99%
“…Loizzo et al (2010) reported the antibacterial activity of total water extract, ethyl acetate and aqueous fractions from the leaves of . Antimicrobial A. heterophyllus activity of the plant extract was considered to be good if its MIC was less than 100µg/ml, moderate if MIC was from 100.0 to 500.0µg/ml and poor over 500.0µg/ml (Dabur et al, 2007). Since the MIC of the methanol extract of the plant against all the microbial strains were less than 100µg/ml, the methanol extract can be considered as a good quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, these extracts were active against V. cholerae NB2, V. cholerae PC2, and S. flexneri which were not sensitive to ampicillin. The antimicrobial activity of a plant extract was considered to be good if its MIC was less than 100.0 μg/mL, moderate if its MIC was from 100.0 to 500.0 μg/mL and poor if its MIC was over 500.0 μg/mL (37). Hence, the MeOH, EtOAc, and n-BuOH extracts of L. leptocarpa exhibited good activity against S. aureus, with an MIC of 64 μg/mL, whereas only the MeOH extract displayed poor activity against V. cholerae SG24(1).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Extracts from most of these herbs have been screened in the search for safer and more effective antibacterial agents [196][197][198][199][200][201].…”
Section: Televancinmentioning
confidence: 99%